2013
DOI: 10.1111/trf.12249
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐related lung injury in children: a case series and review of the literature

Abstract: This study is the largest case series of reported TRALI cases in children. Crude modeling suggests that the incidence of TRALI in children is similar to that of adults. Although the numbers are small, there do not appear to be differences in presentation or outcome between adults and children with TRALI. TRALI is associated with significant morbidity and mortality and pediatricians need to consider this diagnosis in children who experience respiratory distress after transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 32 publications
(33 reference statements)
1
43
0
4
Order By: Relevance
“…These include human errors (wrong product, wrong patient, transfusion of non-irridiated products although indicated) and transmission, even though a rare event, of any virus, protozoa, bacteria, or prion. In general, complications such as transfusion-associated acute lung injury (TRALI) are rare [62], but the incidence is likely to be underestimated especially in ventilated neonates. Transfusion-associated circulatory overload (TACO) may also complicate transfusions in neonates with compromised cardiac function.…”
Section: Outcome Associated With Platelet Transfusionmentioning
confidence: 99%
“…These include human errors (wrong product, wrong patient, transfusion of non-irridiated products although indicated) and transmission, even though a rare event, of any virus, protozoa, bacteria, or prion. In general, complications such as transfusion-associated acute lung injury (TRALI) are rare [62], but the incidence is likely to be underestimated especially in ventilated neonates. Transfusion-associated circulatory overload (TACO) may also complicate transfusions in neonates with compromised cardiac function.…”
Section: Outcome Associated With Platelet Transfusionmentioning
confidence: 99%
“…The study observed that TRALI poses significant risk for mortality and that its accurate diagnosis and extra vigilance is crucial during blood transfusions in children [23].…”
Section: Demographicsmentioning
confidence: 99%
“…Most clinical studies of TRALI have been conducted in operating rooms and ICU, in the form of prospective and retrospective case-control data analyses in critically ill patients in many different settings (Table 2) [3][4][5][17][18][19]21,23,25,26]. Koch et al [27] have primarily examined the effects of transfusion on cardiac patients, observing significant increase in respiratory insufficiency and necessity for mechanical ventilation after transfusion of older RBC units [3,27].…”
Section: Clinical Evidencementioning
confidence: 99%
“…El grupo de hemovigilancia nacional del Reino Unido (SHOT), señaló que el 11% de los casos de TRALI ocurrían en niños entre 2 y 17 años de edad. 7 Se ha propuesto una clasificación atendiendo al tiempo de aparición: TRALI clásica, que comienza durante las primeras 6 h de la transfusión y que coincidiría con el modelo de TRALI inmune y TRALI diferida o tardía, que comienza entre las 6 y las 72 h de la transfusión y cuyo mecanismo de producción sería por mediadores. 10 La TRALI no se relaciona con la edad, sexo, ni se asocia con incompatibilidad de grupo entre donadores y receptores o número de transfusiones previas.…”
Section: Discussionunclassified
“…6 La mayoría de los casos de TRALI se refieren a pacientes adultos. Se estima la frecuencia en la población pediátrica en una de cada 2.000 unidades transfusiones con una tasa de mortalidad de 15% 7 cifras similares a lo publicado en adultos. Ésta se ha relacionado con todos los componentes sanguíneos, aunque con más frecuencia en los que contienen plasma, 8 debido a la presencia de anticuerpos antileucocitarios (TRALI inmune).…”
Section: Introductionunclassified